Volume 3: Design and Manufacturing 2007
DOI: 10.1115/imece2007-42675
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Spot Welding (RSW) of Advanced High Strength Steels (AHSS) for Automotive Body Construction

Abstract: There has been a substantial increase in the use of advanced high strength steel in automotive structures in the last few years. The usage of these materials is projected to grow significantly in the next 5–10 years with new safety and fuel economy regulations. Advanced High Strength Steels (AHSS) are getting popular with superior mechanical properties and weight advantages compared to mild steel materials. These new materials have significant manufacturing challenges, particularly for welding and stamping. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…As mentioned above, one of the major problems regarding RSW of AHSSs is their high probability to fail in interfacial mode. 35,55,[131][132][133][134][135] Failure mode of the spot welds affects their mechanical performance. Some authors 33,136,137 concluded that the load bearing capacity of spot welds is not significantly affected by the failure mode.…”
Section: Failure Mechanism Of Resistance Spot Welds Under Quasi-stati...mentioning
confidence: 99%
“…As mentioned above, one of the major problems regarding RSW of AHSSs is their high probability to fail in interfacial mode. 35,55,[131][132][133][134][135] Failure mode of the spot welds affects their mechanical performance. Some authors 33,136,137 concluded that the load bearing capacity of spot welds is not significantly affected by the failure mode.…”
Section: Failure Mechanism Of Resistance Spot Welds Under Quasi-stati...mentioning
confidence: 99%
“…AHSS steels have higher yield, tensile, and elastic modulus compared to other steel groups. While the tensile strength of high-strength (HSS) steels ranges from 270-700 MPa, the tensile strength of the newly developed high-strength AHSS steel groups exceeds 1000 MPa [16][17][18].…”
Section: Introductionmentioning
confidence: 99%